Identity Development in German Adolescents with and without Visual Impairments. (September 2013) - Pinquart, Martin; Pfeiffer, Jens P.
Introduction: The study reported here assessed the exploration of identity and commitment to an identity in German adolescents with and without visual impairments. Methods: In total, 178 adolescents with visual impairments (blindness or low vision) and 526 sighted adolescents completed the Ego Identity Process Questionnaire. Results: The levels of identity exploration and making commitments, as well as the distribution of identity statuses, did not differ between the two groups. However, adolescents with congenital visual impairments showed lower levels of identity exploration than their peers with acquired visual impairments. In addition, more severe disability was associated with less exploration of identity. Furthermore, levels of identity exploration and commitment varied by age, parental education, levels of social support, and levels of problem behavior. Discussion: The findings indicate that adolescents with visual impairments do not fall behind sighted adolescents in developing a sense of identity. Implications for practitioners: Adolescents who are congenitally blind or have a high level of disability may need support in exploring and accessing information on future opportunities.